Risolvi  3/8 = 6/(5-y)  rispetto a y Risolvi  6/5 + 3/(w-3) = 9/(5·(w-3)) rispetto a w Risolvi  (d+8)/(d-2) = 9/4  rispetto a d Risolvi 4/(x-4) = 7/(x+2)  rispetto a x Risolvi  8/(y-2) - 13/2 = 3/(2y-4)  rispetto a y Risolvi 10/(k-3) + 4/(3-k) = 6  rispetto a k

 Risolvi  3/8 = 6/(5-y)  rispetto a y 3/8*(5-y) = 6 3*(5-y) = 6*8 3*(5-y) = 6*8 5-y = 6*8/3 5-y = 2*8 5-16 = y -11 = y verifica: 3/8 = 6/(5--(11)); 3/8 = 6/16; 3/8 = 3/8: OK Risolvi  6/5 + 3/(w-3) = 9/(5·(w-3)) rispetto a w 6/5*(w-3) + 3 = 9/5 6*(w-3) + 3*5 = 9 6*(w-3) = 9-15 = -6 w-3 = -6/6 = -1 w = -1+3 = 2 verifica: 6/5 + 3/(2-3) = 9/(5·(2-3)); 6/5 - 3 = -9/5; 15/5 = 3; 3 = 3: OK
 Risolvi  (d+8)/(d-2) = 9/4  rispetto a d d+8 = 9/4*(d-2) 4*(d+8) = 9*(d-2) 4d+32 = 9d-18 32+18 = 9d-4d 50 = 5d 10 = d verifica: (10+8)/(10-2) = 9/4; 18/8 = 9/4; 9/4 = 9/4: OK Risolvi 4/(x-4) = 7/(x+2)  rispetto a x 4 = 7/(x+2)*(x-4) 4*(x+2) = 7*(x-4) 4x+8 = 7x-28 8+28 = 7x-4x 36 = 3x 12 = x verifica: 4/(12-4) = 7/(12+2); 4/8 = 7/14; 1/2 = 1/2: OK
 Risolvi  8/(y-2) - 13/2 = 3/(2y-4)  rispetto a y 8/(y-2) - 13/2 = 3/(2*(y-2)) 8 - 13/2*(y-2) = 3/2 8*2 - 13*(y-2) = 3 16 - 13*y + 13*2 = 3 16 + 13*2 - 3 = 13*y 39 = 13*y 3 = y verifica: 8/(3-2) - 13/2 = 3/(2*3-4); 8 - 13/2 = 3/2; 8 = 13/2+3/2; 8 = 16/2: OK Risolvi 10/(k-3) + 4/(3-k) = 6  rispetto a k 10/(k-3) - 4/(k-3) = 6 (10-4)/(k-3) = 6 6/(k-3) = 6 1/(k-3) = 1 k-3 = 1 k = 1+3 = 4 verifica:10/(4-3) + 4/(3-4) = 6; 10-4 = 6: OK